Rural Development Programme Implementation In Developing Countries: The Experience Of China And India (Global Journal of Human-Social Science, 2012)
The crux of this paper is to examine rural development programme implementation in developing countries with China and India as case studies The paper examines various strategies adopted by these countries in the implementation of rural development policies and programmes The study adopts desk research as its methodological orientation The result of the analysis reveals that the Chinese and Indian Governments adopt bottom-up rural development approach which emphasizes involvement of the rural people in rural development programme implementation This strategy has significantly assisted these countries to attain enviable heights in rural development efforts in spite of their increasing population The paper therefore recommends among others the need for China and India to abandon cultural practices belief systems capable of impacting negatively on their rural development programmes and also encourage other developing countries in the third world Africa to emulate the strategies adopted by these two countries in their rural development programme implementation
Keywords: Rural development; Agriculture; Policy; Programme; Implementation